2013
DOI: 10.1037/a0031437
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics and variability in adherence and competence in cognitive-behavioral therapy for panic disorder.

Abstract: Although associations with outcome have been inconsistent, therapist adherence and competence continues to garner attention, particularly within the context of increasing interest in the dissemination, implementation, and sustainability of evidence-based treatments. To date, research on therapist adherence and competence has focused on average levels across therapists. With a few exceptions, research has failed to address multiple sources of variability in adherence and competence, identify important factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
125
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(145 citation statements)
references
References 49 publications
15
125
0
2
Order By: Relevance
“…One reason could be that patients with domineering interpersonal style may present confrontational ruptures in alliance, such as efforts to control the therapist and reject the therapist's formulations or interpretation (Safran, Muran, & Eubanks-Carter, 2011). Such confrontational ruptures may impede the development of a strong alliance and reduce the therapist's opportunities to implement therapeutic techniques competently (as demonstrated by Boswell et al, 2013). It is therefore possible that PD patients with distinct interpersonal styles present different needs in therapy and may benefit from different therapeutic techniques (see also Gude & Hoffart, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…One reason could be that patients with domineering interpersonal style may present confrontational ruptures in alliance, such as efforts to control the therapist and reject the therapist's formulations or interpretation (Safran, Muran, & Eubanks-Carter, 2011). Such confrontational ruptures may impede the development of a strong alliance and reduce the therapist's opportunities to implement therapeutic techniques competently (as demonstrated by Boswell et al, 2013). It is therefore possible that PD patients with distinct interpersonal styles present different needs in therapy and may benefit from different therapeutic techniques (see also Gude & Hoffart, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several recent studies which addressed anxiety disorders also found significant relationships between therapist competence and therapy outcome (r ¼ 0.22-0.79; Westra et al, 2011;Ginzburg et al, 2012;Brown et al, 2013). On the other hand, some studies found no significant relationships between therapist competence and outcome in the treatment of anxiety disorders (e.g., Boswell et al, 2013;Huppert et al, 2001). However, inappropriate methodological approaches, like the evaluation of therapist competence with only one global item might be responsible for the heterogeneous findings in research (Simons et al, 2013;Webb et al, 2010;Weck et al, 2011a).…”
Section: Introductionmentioning
confidence: 92%
“…First, previous research indicates that therapists are often less adherent to treatment protocols when working with aggressive patients, possibly due to patient hostility or therapist-rejecting behaviors in session. Second, these protocols are not designed to address aggression in the context of an anxiety disorder 21 . Therefore, when a patient with PD and higher than average aggression is identified at their intake assessment, therapists could decide to target aggressive behaviors early in treatment, which may increase patients’ chances of more broadly benefitting from (and completing) a PD-focused treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Existing, albeit limited, research suggests that, similar to aggression in other anxiety disorders, aggression in PD is associated with greater symptom severity, impulsivity, and suicide risk 20 . In treatment, higher scores on patient aggression are associated with lower ratings of therapist adherence to treatment protocols, suggesting that patients with higher aggression and hostility may be engaging in treatment- or therapist-rejecting behaviors that could reduce the effectiveness of the treatment being delivered 21 .…”
Section: Introductionmentioning
confidence: 99%